Atividade da beta-glucuronidase no suco gástrico e mucosa gástrica de ratos submetidos a carência proteica - Rezende, T. A. de; Ribeiro, M. A. C. L.; Campana, A. O. (My University, 1979)
An experiment was performed in order to evaluate the beta-glucuronidase activity in gastric juice and gastric mucosa of rats submitted to a protein-free diet. A group of 36 young adult male Wistar rats was fed a protein-free diet ad libitum for five weeks; a second group of 36 Wistar rats ingested a purified isocaloric 12,5% casein diet for the same period. The concentration of proteins in plasma, gastric juice and gastric glandular mucosa and the beta-glucuronidase activity in the gastric juice and gastric glandular mucosa were determined. Protein deficient rats had lower plasma protein concentrations and also lower protein concentrations in gastric juice and gastric mucosa. In these animals there was no significant change of beta-glucuronidase activity in the gastric juice, but there was a significant increase of the specific enzymatic activity in the gastric mucosa. The results suggest that protein restriction in young adult rats affects the gastric mucosa. The increase of the specific beta-glucuronidase activity might be due to heightened local catabolism or to a comparatively more severe protein depletion.
Beta-glucuronidase activity in gastric juice and gastric mucosa of rats submitted to protein deficiency
Keywords: beta glucuronidase; animal experiment; hypoproteinemia; rat; stomach; stomach juice; stomach mucosa; theoretical study; Animal; Blood Proteins; Body Weight; English Abstract; Gastric Juice; Gastric Mucosa; Glucuronidase; Hydrogen-Ion Concentration; Male; Protein Deficiency; Rats